12-Leads Electrocardiogram Interpretation Competency among Nurses working in Critical Care Areas at Dow University Hospital, Karachi - Nadeemuddin; Yaqoob, Muhammad; Ali, Amjad; Siddiqui, Faraz; Rehan, Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To assess the 12-lead Electrocardiograph (ECG) interpretation competency level of nurses working in the critical care units of Dow University Hospital, Karachi. METHODOLOGY: The descriptive cross-sectional design study was conducted from October to December 2019. The purposive sampling technique was used to include the participants. The study sample constitutes 120 registered nurses from the critical care units of Dow University Hospital (DUH), including the intensive care unit (ICU), coronary care unit (CCU), and emergency department(ED). Full-time Registered nurses with more than one year of professional experience and currently working in critical care units of Dow University Hospital were included, and those with post-basic-cardiology specialization were excluded. Data were collected through a 12-item validated study questionnaire and analyzed through descriptive statistics using SPSS version 21.0. RESULTS: Most of the participants, 84 (70.0%) in this study, were male, and 46(38.3%) of the nurses have completed Post RN-BS Nursing (post-diploma two years undergraduate nursing degree program) as the highest professional qualification. This study determined ECG interpretation competence as a score of ? 9 out of 12. The findings of this study revealed that 38(31.66%) nurses scored ? 9, whereas 82 (69.34%) nurses scored eight or less. CONCLUSION: The study found that most nurses performing their duties in critical hospital areas have suboptimal ECG interpretation competency levels. A relatively higher level of competency was found among nurses working in CCU.